ANALISA DAYA DAN KONTROL KECEPATAN MOTOR PADA ALAT BANTU LAS ROTARY POSITIONER TABLE - Saptono, Hery; Pramono, Gatot Eka; Khindi, Hablinur Al (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
Rotary Positioner Table is one of the welding aids that are widely used industrial world especially welding with the intention of facilitating welder to work on certain products. As the name implies Positioner which means positioning where the tool in this design can position the welding object freely according to the correct position and comfortable for people who are doing welding. This tool can be applied to drill the hole circle the same distance on the flange, to cut the round pieces , for welding pipes, welding shafts, discs, truck rims, etc.The selection of motor types and speed control becomes very important to support the performance of this tool which is expected to be used for welding with a maximum work load of 100 kg with vertical welding position. For that matter proper analysis is needed to determine the motor power and rotation speed of the turntable in order to get the best welding results. The way this Positioner tool works mechanically by rotating the rotary axis (lever) that has been made, to adjust the angle manually. This positioner can move on the X, Y, and Z axes.